Virtual Obstetric Psychoprophylaxis Program and the Attitude of Adult Pregnant Women during Labor in the EsSalud Tarapoto Hospital, 2020. - Cárdenas-Macedo, Gissela Giovana (2023)
Introduction. The pregnant woman's behavior during labor is influenced by her experience, culture, and idiosyncrasy, making her the protagonist of her own physiological process. Pregnant women often feel fear during labor when they are attended to by a healthcare team in a hospital setting, which can lead to maternal-fetal complications if their anxiety is exacerbated by the pandemic. Cultural influences and women's limited knowledge about the reproductive process contribute to a state of fear, distress, and tension, leading them to perceive childbirth as a painful event. Objective. To establish the relationship between the Virtual Obstetric Psychoprophylaxis Program and the Attitude of Adult Pregnant Women during labor in the EsSalud Tarapoto Hospital. Materials and Methods. This study was quantitative, non-experimental, descriptive, and prospective with a cross-sectional design. A descriptive-correlational design was used, and the subjects included in the study groups were selected through non-probabilistic sampling, as determined by the researcher considering the entire population. A sample of 50 pregnant women was included. The data collection techniques used were surveys and observation sheets, with the questionnaire and Likert scale as the applied instruments. Results. The results of the study on the Virtual Obstetric Psychoprophylaxis Program and the attitude of adult pregnant women during labor in the EsSalud Tarapoto Hospital showed that 75.0% of the pregnant women had a favorable attitude during labor, while 25.0% had an unfavorable attitude. Conclusions. There is a significant relationship between the Virtual Obstetric Psychoprophylaxis Program and the attitude of adult pregnant women during labor in the pandemic, as statistically confirmed (p<0.05).